Energy savings in residential air conditioners using condensate cooling in discharge and liquid lines - Yuningsih, Nani; Sumeru, Kasni; Aldiansyah, Muhammad; Tritjahjono, Rachmad Imbang; Nugraha, Fathurahman Yudhi; Abioye, Adenkunle Moshood (Politeknik Negeri Lhokseumawe, 2025)
This research investigates the use of condensate produced by the evaporator to cool the discharge and liquid lines in order to reduce electricity consumption in a residential split-type air conditioner (AC). The experimental setup used a 0.75 kW compressor with R32 refrigerant, where the discharge and liquid line heat exchangers were 20 cm and 15 cm long, respectively. Data were collected over 180 minutes at 5-minute intervals. Results show that using the liquid line cooler (LLC) alone reduced electricity consumption by 5.3% and increased cooling capacity by 2.3%. Using the discharge line cooler (DLC) alone reduced electricity consumption by 8.3% and increased cooling capacity by 7.3%. When both coolers were applied simultaneously (LDC mode), electricity consumption decreased by 10.9% and cooling capacity increased by 9.7%. The corresponding improvements in coefficient of performance (COP) were 9.1% (LLC), 18.6% (DLC), and 24.7% (LDC). These results indicate that using condensate to both the discharge and liquid lines is more effective in reducing electricity consumption and improving AC performance than cooling only one line.